Design and Development of an Application for Recording Income and Expenditure Data at Darrel's Cake Shop Prabumulih City - Seftivia, Nadyah; Muchlis; Nurmayanti (Jurnal Teknologi Informatika dan Komputer, 2025)
Technology is a combination of skills, knowledge, equipment, machines and computers used to design, produce and distribute goods and services. These technological advances have made many companies, organizations, traders and agencies use computer-based technology so that their work is more effective and efficient. Many institutions or traders have used the system to record their income and expenses. Technological advances have made many companies, organizations, traders and agencies use computer-based technology so that work is more effective and efficient. Darrell's Cake Shop is part of the ready-made food industry which is one of the centers for typical souvenirs in Prabumulih City. There are two ways to sell at the Darell Cake Shop, the first is for consumers to come to the shop, and the second is to order online.  The process of recording income and expenditure data is still done manually by writing in a book, this is of course less effective which will cause errors and difficulties in finding out income and expenditure reports. The aim of this research is to create an application for recording income and expenditure data at Darrell's Cake Shop, Prabumulih City. The research method uses a qualitative descriptive method with data collection techniques in the form of interviews, observation and literature study. Data types consist of qualitative data and data sources consist of primary data and secondary data. Waterfall development method. This application was built on the basis of the Visual Basic programming language. Net designed using Microsoft Visual Studio 2010.